PrefWS3: Web services selection system based on semantics and user preferences (Informatica, 2016)
With the growing number of web services on the Web, many approaches have been proposed to help users discover and select the desired services. Nevertheless, finding the best service that meets the user needs and preferences is still a problem. In this article, we introduce a user preferences based semantic web services discovery and selection system (PrefWS3). PrefWS3 is considered to be a user-centric system which helps users in formulating their requirements and preferences. This system involves semantic enhancement of both request and web services and provides an efficient semantic-based matching mechanism, which calculates the semantic similarity between the request and the web service. Furthermore, PrefWS3 includes a QoS-aware process and provides a reputation mechanism that enables users to evaluate the credibility of the web services they use. In this article, we also present the results of a comparison of the PrefWS3 and some other published approaches to evaluate its effectiveness.